Success and Failure of Implant in Bounded and Free End Saddle Area - Nadira A Hatim; Rawa Y Al-Rawee; Bashar A Tawfeeq (University of Mosul, College of Dentistry, 2010)
Aims: To investigate age and site distribution (bounded and free end extension saddle area), and the most common width of implant can be used to give a successful results. Determine the percentage and the causes of implant failure. Materials and Methods: One hundred seventeen patients were chosen to undergo implant surgery in Al-Salam Hospital Implant Center with age group (17 y-above 60y). Frialit-2 Implant system is used with its different length and width. Post surgical follow up of patients were for 2 days, 1 week, 2 weeks after operation, and each month periodically for 6 months. History, inspection and palpation of the edentulous area considered in order to check pain, paraesthesia, in-flammatory process, infection. Post prosthetic follow up of the patients were for a period ranged from 6 month to 7 years, according to clinical and radio graphical examination of the patient. Results: clinical analysis of 117 patients was second and third decades of life ranged from 17- 40 Ys (77.77 %) with 142 implants (59.91%). One hundred forty four implants were seated in the maxilla different regions while ninety three implants seated in the mandible (Bounded and free end). Three different widths (3.8, 4.5, and 5.5 mm) were used according to the criteria of patients , and Ferialit II System. Conclusion: Higher range of age needs implant (3.8mm) was between 17- 40 years. The success rate in the maxilla was less than mandible. Slight difference was in percentage of success between bounded and free end extension partially missing teeth. The causes of failures were related to poor bone quantity specially in the maxillary arch, Surgical error in implant positioning, poor attitude of the patient to use denture be-fore reliving the area , and Poor fellow up of the patient after gingival former.